Características clínicas e evolução de crianças com doenças inflamatórias intestinais de início muito precoce - Silva, Natália Oliveira e [UNIFESP] (2016)
Objective: To evaluate clinical patterns and outcome of early-onset inflammatory bowel disease - diagnosis before 6 years of life - and very early-onset - diagnosis before 2 years. Methods: From a total of 278 patients followed in a single center of Inflammatory Bowel Disease, 14 children were diagnosed under the age of 6 and 25 between 2 and 6 years old. A control group of 39 children and adolescents ages between 6 and 18 years, were selected to compare to each early-onset and very early-onsed patients. We analyzed clinical characteristics at diagnosis and disease activity index, laboratory assay and nutritional status at diagnosis and after 1 year of treatment. Extra-intestinal manifestations, clinical and surgical therapy during the follow-up to March 2016, and disease location, as described by The Paris Classification, were analysed. Results: Crohn's disease (CD) was more frequent among children with very early onset. Very early-onset group had lower height-for-age z score at diagnosis and lower levels of hemoglobin, higher leukocytes, platelets, ESR and disease activity index after 1 year follow-up in relation to those starting after 6 years. Children under 2 years showed a higher proportion of a history of cow's milk protein allergy than the others groups. Perianal fistula was common among early-onset and very early-onset group. Conclusion: We present a high frequency of children with very early-onset CD. Very early-onset CD present a higher frequency of height deficit at the time of diagnosis and more severe inflammation, confirmed by laboratory tests, them the group older than 6. Cow's milk protein allergy was more frequent in children under 2 years then those between 2 and 6 and older than 6 years.